Knowledge of Female Dental Students of KKU Regarding Pulp Revascularization Treatment - Fariha Naz, Muhammad Qasim, Nadia Munir, Abdul Samad Khan, Sana Chaudhry, Manal Hussain Alshahrani, Sara Ali Alshahrani, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the knowledge of female dental students of KKU about pulp revascularization procedure. Methods: A self-administered questionnaire was distributed to female students of 5th and 6th year and to dental interns. Collected data were analysed with descriptive statistics using SPSS (V19). Results: 137 contributors filled the proforma. Highest percentage of students (35%) considered pulp revascularization as the best treatment for immature necrotic permanent teeth in terms of tooth survival and 45.3% believed to have strongest tooth structure with this procedure as compared to other options. 68.6% of the participants had never attempted this procedure. 53.3% of the students were not sure about the outcome of the treatment. Only 31.4% of the students were aware of need of post and core as a contraindication forprocedure. 52.6% participants chose the option of little instrumentation with sodium hypochlorite irrigation for canal cleaning and 27.7% considered CaOH as a best intracanal medicament. According to majority of students (44.5%) continued root development with absence of signs and symptoms were the best indications of successful treatment. Conclusion: Majority of the students had the knowledge of regenerative endodontics as a viable treatment option for immature permanent teeth with necrotic pulps but were unaware of the details of the procedure and case selection criterion. Students should be given detailed clinical knowledge of this procedure so that in their future clinical practice they consider it among other options either for treatment or do case selection for referrals to specialists. Keywords: pulp revascularization; knowledge; dental students.